PENGARUH PROFESIONALISME, PENGETAHUAN AUDITOR DALAM MENDETEKSI KEKELIRUAN, INDEPENDENSI DAN PENGALAMAN AUDITOR TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS DALAM AUDIT LAPORAN KEUANGAN DENGAN ETIKA PROFESI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada BPK - Suci Oktavia; Emrinaldi Nur DP; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyze and gets emprical prove of the influence of the professionalism, the auditor’s in detecting errors, independence and auditor experience to the consideration on materiality level in the audit of financial statements with professional ethics as moderating variable. Respondents in this research is the auditor’s who work on BPK RI representative west sumatera province.The sample of this research 52 auditor’s. The research used primary data which was obtained from the answer of the respondents and the questionnaire distributed. The hypothesis test in this research of analysis by using multiple linear regression, test using SPSS software version 20 to process data. The results of this research indicate that the professionalism, the auditor’s knowledge in detecting errors, independence and auditor experience significant effect to the consideration in materiality level on the audit of financial statements. Then, the interaction of professional ethics and professionalism, the auditor’s knowledge in detecting errors, independence, auditor experience significant effect to the consideration in materiality level on the audit of financial statement.Keywords: Professionalism, Errors, Independence, Experience, and Materiality